Social reactions to disclosure and perceived social support are each uniquely associated with mental health in the first 6 months following sexual assault - Thoresen, Siri; Blix, Ines; Johnsen, Grethe E.; Wentzel-Larsen, Tore; Ullman, Sarah E. (Frontiers in Psychology, 2025)
IntroductionIt is well-known that social support is related to mental health following sexual assault (SA). Recent research suggests that social reactions to disclosure may also affect mental health; however, few studies have accounted for general social support, and most have been conducted many years after the assault. This study aimed to examine whether social reactions are uniquely linked to mental health when adjusting for perceived social support in recent victims of SA.MethodsIn this cross-sectional study, participants were recruited from Sexual Assault Centers (SACs) and through social media. The sample comprised 173 female participants (mean age = 26 years, SD = 8.6) who had experienced a SA within the last 6 months and had disclosed the SA to someone. We used linear regression analyses to assess associations between social reactions to disclosure, social support, and post-traumatic stress reactions (PTSR) and anxiety/depression symptoms.ResultsAlthough positive social reactions to disclosure were most common, negative social reactions were highly prevalent even in this early phase after SA. Negative social reactions of the Unsupportive acknowledgment type were significantly associated with more PTSR (b = 0.36, 95% CI = 0.14, 0.57), while perceived social support was significantly associated with fewer symptoms of anxiety/depression (b = −0.20, 95% CI = −0.32, −0.08).ConclusionsSocial reactions and social support were differentially associated with PTSR and anxiety/depression symptoms, indicating that certain aspects of social relationships may play different roles in the recovery process. Our results call for early interventions following SA to reduce negative reactions to disclosure and facilitate the provision of positive social support to victims.